ACCOUNTING FOR AGRICULTURAL ACTIVITY: HOW TRANSPARENT ARE SERBIAN COMPANIES? - Vasilić, Marina; Savić, Bojan (Economics of Agriculture, 2025)
In this study, we analyze compliance with global professional accounting regulation in a sample of Serbian agricultural companies. Focusing on key mandatory disclosures related to biological assets, we calculate the companies’ annual and average Disclosure Scores and find significant non- compliance. Despite the adoption of International Financial Reporting Standards (IFRS) as the “gold standard” for high- quality financial reporting, company management fails to provide transparent disclosures in the financial statements, underscoring the importance of country- and company- specific determinants of financial reporting quality. We identify that variations in financial transparency can be explained by differences in the company’s reporting framework, type of auditor, and ownership structure, while the effects of company size and legal form remain inconclusive. The findings of our research may be valuable to investors, corporate managers, regulators, and future researchers looking at the quality of financial reporting on agricultural activity.